2016
DOI: 10.1155/2016/3124960
|View full text |Cite
|
Sign up to set email alerts
|

Role of T-Cell Polarization and Inflammation and Their Modulation by n-3 Fatty Acids in Gestational Diabetes and Macrosomia

Abstract: Th (T helper) cells are differentiated into either Th1 or Th2 phenotype. It is generally considered that Th1 phenotype is proinflammatory, whereas Th2 phenotype exerts anti-inflammatory or protective effects. Gestational diabetes mellitus (GDM) has been associated with a decreased Th1 phenotype, whereas macrosomia is marked with high expression of Th1 cytokines. Besides, these two pathological situations are marked with high concentrations of inflammatory mediators like tumor necrosis factor-α (TNF-α) and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…T cells (responsible for cell-mediated immunity) have been shown to play a critical role in GDM and macrosomia [ 13 , 17 , 18 ]. T cells can be divided into two subsets: T helper cells (CD4+) and T cytotoxic cells (CD8+).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…T cells (responsible for cell-mediated immunity) have been shown to play a critical role in GDM and macrosomia [ 13 , 17 , 18 ]. T cells can be divided into two subsets: T helper cells (CD4+) and T cytotoxic cells (CD8+).…”
Section: Discussionmentioning
confidence: 99%
“…They observed a very high level of proinflammatory cytokines, IFNg and IL2, in obese and diabetic animals [ 18 ]. In gestational diabetic women, some authors have shown that low Th1 concentrations and high IL-10 levels may be implicated in maintaining the pregnancy [ 13 , 17 , 20 ]. Besides, recent data have suggested the protective role of IL-10 against inflammation in adipose tissue and insulin resistance [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to GDM-d, we found no differences in protein expression for any of the vitamin D metabolic components between GDM-i and NG placental tissues. The lack of difference between GDM-i and NG groups could be explained by the anti-inflammatory properties of insulin [50, 51]. It is possible that the inflammatory state is decreased at the feto-maternal interface in GDM-i women compared with GDM-d women.…”
Section: Discussionmentioning
confidence: 99%